Competing on analytics the new science of winning - Davenport, Thomas H. 1954-; Harris, Jeanne G. (Harvard Business Review Press, 2017)
Leading companies are doing more than just collecting and storing data in large quantities--they're now driving their competitive strategies based on data-driven insights. And achieving impressive results: Identifying the most profitable customers, accelerating product innovation, optimizing supply chains and pricing, and leveraging the true drivers of financial performance. The secret weapon? Analytics--sophisticated quantitative and statistical analysis and predictive modeling supported by data-savvy leaders and powerful information technology. In Competing on Analytics, Davenport and Harris explain how analytics are transforming the basis of competition in industry after industry. They show how organizations as diverse as Procter & Gamble, Capital One, CEMEX, and the Boston Red Sox are using these tools to outperform rivals, by applying analytics to finance, manufacturing, R&D, HR, and with customers and suppliers. Presenting a practical framework of the five stages of analytical competition, this book provides managers with the roadmap for becoming an analytical competitor.-- Provided by publisher